Penerapan Praktis Analisis Fundamental - Dwi Kartikasari (Politeknik Negeri Batam, 2013)
To be a successful investor, learning fundamental analysis is the first step in selecting stocks. Therefore, the author hopes this article can describe the implementation of fundamental analysis on a stock in a practical and comprehensive manner using the research style of the Burkenroad Reports that has been wellknown to the world for the quality of the report, the well-performed track record, and the independent opinion. The research method applied in this study is a case study on Bristow Group Inc. whose shares are traded on the New York Stock Exchange. Research on Bristow started from August 2012 to February 2013 using interviews, field survey and literature review. Data were analyzed using descriptive qualitative and quantitative techniques. Linear regressionmethod is used to project the company's revenue and time series method is used to predict the growth of the company's assets. Fundamental analysis consists of economic analysis, industry analysis, and analysis of the company, followed by a comparative analysis. Industrial analysis used is Porter's five forces analysis and risk analysis of the industry. The valuation of the company uses discounted cash flow method, the relative value comparison methods, and dividends model. In addition to the three above analysis, this research also collects comparative analysis through the analysis of Ben Graham, Altman, investor composition analysis, and recommendations from other stock analysts. Based on the fundamental analysis, the author predicted price increase to 54 from the current price of 49.48. The author suggests to hold Bristow shares at the end of the study period for stocks are predicted to rise in the next year with growth rate of less than 20 percent